2019
DOI: 10.21203/rs.2.11703/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of serum low-density lipoprotein and systolic blood pressure levels with type 2 diabetic patients with and without peripheral neuropathy: Systemic review, meta-analysis and meta-regression analysis of observational studies

Abstract: Background:Compositional abnormalities in lipoproteins and cardiovascular risk factors play an important role in the progression of diabetic peripheral neuropathy (DPN). This systematic review aimed to estimate the predicting value of low-density lipoprotein (LDL) and systolic blood pressure (SBP) level in type-2 diabetes mellitus (T2DM) patients with and without peripheral neuropathy. We also tried to determine whether LDL and SBP are associated with an increased collision risk of DPN. Materials and Methods:… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…As shown in the present study, SBP was one of the risk factors for DPN among patients withT2DM, consistent with previous studies. A systematic review showed a 2.6-fold higher SBP in T2DM patients with DPN than in T2DM patients without DPN [9]. Regardless of whether T2DM is accompanied by hypertension, an elevated SBP always increased the risk of DPN [10].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the present study, SBP was one of the risk factors for DPN among patients withT2DM, consistent with previous studies. A systematic review showed a 2.6-fold higher SBP in T2DM patients with DPN than in T2DM patients without DPN [9]. Regardless of whether T2DM is accompanied by hypertension, an elevated SBP always increased the risk of DPN [10].…”
Section: Discussionmentioning
confidence: 99%